2004
DOI: 10.1007/s00330-004-2301-9
|View full text |Cite
|
Sign up to set email alerts
|

Dose reduction in subsecond multislice spiral CT examination of children by online tube current modulation

Abstract: The potential of online tube current modulation in subsecond multislice spiral CT (MSCT) examinations of children to reduce the dose without a loss in image quality is investigated in a controlled patient study. The dose can be reduced for oval patient sectional view without an increase in noise if the tube current is reduced where the patient diameter and, consequently, attenuation are small. We investigated a product version of an online control for tube current in a SOMATOM Sensation 4 (Siemens, Forchheim).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(58 citation statements)
references
References 15 publications
1
55
1
1
Order By: Relevance
“…Reduction of radiation exposure was possible in our study through the use of an online modulation of tube current implemented with the 16 -detector row CT scanner for all 16 -detector row CT angiograms. Greess (26) demonstrated a reduction of the effective dose from 26% to 43% in children on the basis of the patient's body shape and weight by using a multi-detector row CT scanner with an attenuation-based online modulation of the tube current. For the pelvis and extremities, a mean effective dose reduction of 25% and 39%, respectively, could be obtained in another study by using a single-detector row CT scanner and attenuation-based on-line modulation of the tube current (27).…”
Section: Discussionmentioning
confidence: 99%
“…Reduction of radiation exposure was possible in our study through the use of an online modulation of tube current implemented with the 16 -detector row CT scanner for all 16 -detector row CT angiograms. Greess (26) demonstrated a reduction of the effective dose from 26% to 43% in children on the basis of the patient's body shape and weight by using a multi-detector row CT scanner with an attenuation-based online modulation of the tube current. For the pelvis and extremities, a mean effective dose reduction of 25% and 39%, respectively, could be obtained in another study by using a single-detector row CT scanner and attenuation-based on-line modulation of the tube current (27).…”
Section: Discussionmentioning
confidence: 99%
“…Higher tube current will give more radiation dose to patients [4,6]. Thus, adjustment of tube current based on patient size will reduce the radiation dose to patients especially in paediatric patients [24,25]. Furthermore, other CT imaging parameters such as tube voltage, pitch, time per bed and rotation can be adjusted manually to obtain good images [22] rather than rely on AEC function only.…”
Section: Resultsmentioning
confidence: 99%
“…As we wanted to specifically evaluate the influence of slice thickness and table speed on the detection of low contrast lesions, we used the same radiation dose for the four protocols. The CTDIw applied was adapted to the recommended dose for abdominal CT by the European Guidelines, which suggest CTDIvol values ranging from 17.5 to 29.5 mGy for liver screening investigation [17][18][19][20][21]. In addition, in a previous experimental study performed with a phantom simulating the X-ray absorption of a standard abdomen, it has been demonstrated that for the detection of 5 mm lesions to achieve a CNR of 1, which ensures a detection rate of 100%, the X-ray dose required correspond to a CTDIw=20 mGy [11].…”
Section: Discussionmentioning
confidence: 99%